Antarctic lake phytoplankton and bacteria from near‐surface waters exhibit high sensitivity to climate‐driven disturbance - Shasten Sherwell; Isha Kalra; Wei Li; Diane M. McKnight; John C. Priscu; Rachael M. Morgan‐Kiss (Environmental Microbiology, 2022)
The McMurdo Dry Valleys (MDVs), Antarctica, represent a cold, desert ecosystem poised on the threshold of melting and freezing water. The MDVs have experienced dramatic signs of climatic change, most notably a warm austral summer in 2001–2002 that caused widespread flooding, partial ice cover loss and lake level rise. To understand the impact of these climatic disturbances on lake microbial communities, we simulated lake level rise and ice‐cover loss by transplanting dialysis‐bagged communities from selected depths to other locations in the water column or to an open water perimeter moat. Bacteria and eukaryote communities residing in the surface waters (5 m) exhibited shifts in community composition when exposed to either disturbance, while microbial communities from below the surface were largely unaffected by the transplant. We also observed an accumulation of labile dissolved organic carbon in the transplanted surface communities. In addition, there were taxa‐specific sensitivities: cryptophytes and Actinobacteria were highly sensitive particularly to the moat transplant, while chlorophytes and several bacterial taxa increased in relative abundance or were unaffected. Our results reveal that future climate‐driven disturbances will likely undermine the stability and productivity of MDV lake phytoplankton and bacterial communities in the surface waters of this extreme environment.